Food Consumption Pattern and Lifestyle Modification Traits in Relation to the Level of Stress among Individuals of Uttarakhand, India - Bisht, Anju T.; Kukreti, Vallari T. (International Journal of Social Sciences and Management, 2016)
The increase in the stress generated psychophysiological disorders promotes a probe into the influence of lifestyle modification factors and food consumption on stress .Hence, the present study aims to study, firstly, the impact of lifestyle modification factors on stress in reference to sex and secondly, the frequency of the consumption of major food groups by individuals experiencing various levels of stress in reference to sex. An exploratory study comprising a sample of 117 individuals (62females and 55 males) of age range 22-55years was conducted in Uttarakhand, India. PSSI was administered for assessing the levels of stress. Questionnaires were developed for identifying lifestyle modification factors and food consumption pattern. Mean scores and percentages were employed to describe the data. t-test and χ² were deployed for the assessment of significant difference. Non vegetarian females, male smokers and alcoholics of both the sexes revealed higher stress than their counterparts. Females consuming junk and market food had lower stress than those females who were not consuming the same. Contrary to the females, males consuming junk and market food had higher stress levels than the males who were not consuming junk and market food. Significant differences were found in the stress levels of males who consumed roots and tubers, milk based products and saturated fats. Further studies with larger sample size are required. Int. J. Soc. Sc. Manage. Vol. 3, Issue-4: 239-245